Utilizations, vulnerability and conservation practices of Saba senegalensis (A. DC.) Pichon (Apocynaceae), a high value local species in Burkina Faso Utilisations, vulnérabilité et practiques de conservation de Saba senegalensis (A. DC.) Pichon (Apocynaceae), une espèce locale à haute valeur socio-économique au Burkina Faso - Diawara, Sata; SAVADOGO, Patrice; SANOU, Lassina; OUEDRAOGO, Amadé; Kabre, Blaise (Ethnobotany Research and Applications, 2022)
Background: Saba senegalensis is a woody liana that provides medicinal products, food, income and ecological benefit (soil and water conservation) to the populations in sub-Saharan Africa. In Burkina Faso, the species is mismanaged by the local population, but few studies have been conducted on its uses. This study seeks to understand the local knowledge of S. senegalensis uses and its vulnerability. Methods: Semi-structured ethnobotanical surveys were conducted in the provinces characterized by slightly (Houet), moderately (Mouhoun) and severely (Yatenga) dry climate in Burkina Faso. A total of 180 randomly selected individuals responded to the questionnaire. Socio-demographic characteristics of the informants, the plant parts used, and the categories of uses were recorded. Analyses included an index of uses and vulnerability, importance values of plant parts used, and frequency calculations. Results: Local knowledge of S. senegalensis uses varied according to the locality and informant age. Seven use categories were identified: traditional medicine, food, construction, fodder, handicrafts, domestic energy, and magic. All vegetative organs of S. senegalensis are used. The species’ vulnerability index (IV=2.75) is higher than 2.50, making it vulnerable. The leaves and tendrils plant are the most common plant parts used in traditional medicines. Generally, crude drugs are used in the form of decoction, followed by infusion forms. The diversity of medicinal uses of S. senegalensis highlights the need for future ethno-pharmacological studies of the species. Exploitation of the fruits of the species contributes substantially to food and nutritional security and to improving the living conditions of local populations. Conclusion: Our findings provide essential information for decision-making for effective domestication initiatives for S. senegalensis. The findings also provide a baseline for future research into the development of value chains for the species. They also draw attention to the need for conservation measures for the plant. Keywords: Local knowledge; wild fruit tree; goose liana; forest products; use category; metric index; vulnerability index. Resumé Contexte : La liane goïne (Saba senegalensis) est une liane ligneuse qui fournit des médicaments, de la nourriture, des revenus et des avantages écologiques (conservation des sols et de l'eau) aux populations d'Afrique subsaharienne. Au Burkina Faso, l’espèce est mal exploitée par les populations locales alors que peu d’études se sont intéressées sur ses usages. L’objectif de la présente étude est d’appréhender les connaissances locales sur S. senegalensis et les pratiques qui sont source de sa vulnérabilité. Méthodes: La collecte des données s’est faite au moyen d’interviews semi-structurées conduites dans les provinces caractérisées par un climat légèrement (Houet), modérément (Mouhoun) et sévèrement (Yatenga) sec au Burkina Faso. Au total, 180 personnes choisies de manière aléatoire ont répondu au questionnaire. Les caractéristiques sociodémographiques des informateurs, les organes utilisés de la plante et les domaines d’utilisation ont été recensés. Le traitement des données a consisté en des calculs de fréquences et des indices de valeurs d’usage, d’importance et de vulnérabilité (IV) des organes de l’espèce. Résultats : Les résultats ont montré que les connaissances locales relatives aux usages de S. senegalensis varient suivant les localités et l’âge des répondants. L’espèce est sollicitée dans sept domaines d’usage que sont : la médecine traditionnelle, l’alimentation, la construction, le fourrage, l’artisanat, l’énergie domestique et socio-culturel. Tous les organes de la plante sont utilisés. L’indice de vulnérabilité (IV = 2,75) est supérieur à 2,50 classant ainsi l’espèce comme très vulnérable. Les feuilles et les vrilles sont les organes les plus couramment utilisées dans la médecine traditionnelle. Généralement, les médicaments à l’état brut sont utilisés sous forme de décoction, suivie de formes d'infusion. La diversité des usages médicinaux de l’espèce constitue un atout pour la valorisation de ses propriétés médicinales à travers des études ethno-pharmacologiques. En plus des usages médicinaux, l’exploitation des fruits de l’espèce contribue substantiellement à l’amélioration de la sécurité alimentaire et nutritionnelle et des revenus des populations locales. Conclusion: Nos résultats fournissent des information de base pours des recherches futures en vue du développement de chaînes de valeur de l’espèce à travers la mise en place d’une véritable filière. Aussi, ils attirent l’attention sur la nécessité de prise de mesures pour la conservation de la plante. Mots clés: Connaissances locales, fruitier sauvage, liane goïne, Produits forestiers, domaine d’usage, indice métrique, indice de vulnérabilité.